Lived Experiences of Nursing Students and Educators on Self-Management in Teaching and Learning in Ghana: An Interpretive Phenomenological Study - Mercy Kokuro PhD (Nursing), M Nursing, Diploma (Education), BSc (Nursing), Diploma (Nursing); Talitha Crowley RN, PhD; Anita Serdyn van der Merwe BSocSc Hons (Nursing), MSocSc (Intensive Care Nursing), PhD (Nursing), BA Hons (Philosophy); Cornelle Young BA Nurs, B Hons Nurs, MCur, D Litt et Phil, RN (SAGE Open Nursing)
Introduction As students enter nursing education, they shift away from parental control and school support, taking responsibility for themselves and their academic performance. This independence requires self-management abilities. However, few studies have explored the experiences of nursing students and educators on self-management in the teaching and learning. Objective The study aimed to understand the lived experiences of self-management in teaching and learning context from the perspectives of nursing students and educators from different nursing colleges in Ghana. Method A qualitative interpretive phenomenological approach was used. Individual in-depth interviews were conducted with 17 first- and third-year nursing students and eight nurse educators. Verbatim transcriptions were analyzed using the steps of the interpretive process and the hermeneutic circle, with continual review and analysis between the parts and the whole. Results This study explored self-management in the teaching and learning context among nursing students, revealing four major themes: strategizing for progress and success, nurturing health and well-being, developing self-belief, and partnering with others, each with associated subthemes. The findings indicate that self-management elements are deeply interconnected and interdependent. Strategizing for progress and success involves time management, goal setting, self-discipline, and continuous self-evaluation. Nurturing health and well-being is essential for a sound mind and body through self-care. Developing self-belief, including confidence and self-assurance, is key to academic success. Both students and educators emphasized partnering with others, highlighting collaborative learning and support networks as crucial to self-management in nursing education. Conclusion These themes provide valuable insights for nursing students, educators, and institutions by shedding light on their experiences with self-management in teaching and learning. By understanding these perspectives, educators and institutions can implement innovative teaching approaches that effectively support students in developing self-management skills.